The Influence of Talent Management, Principal Leadership, and Student Interest on Student Participation in Extracurricular Activities at High Schools in Mandau Subdistrict, Bengkalis Regency, Riau Province - Siska Engriani Nasution; Maya Novita Sari (Journal of Educational Sciences, 2026)
This study aims to analyze the influence of talent management, principal leadership, and student interest on student participation in extracurricular activities at senior high schools (SMA) in Mandau Subdistrict, Bengkalis Regency, Riau Province. The study employed a quantitative approach using an explanatory survey method. The study population consisted of 1,049 students participating in extracurricular activities, with a sample of 392 students selected using simple random sampling. Data were collected via a closed-ended questionnaire using a Likert scale and analyzed using simple linear regression and multiple linear regression with IBM SPSS Statistics 26. The results indicate that talent management and the principal’s leadership have a partial positive but insignificant effect on student participation, with significance values of 0.225 and 0.335, respectively (p > 0.05). Conversely, student interest had a positive and significant effect on student participation with a significance value of 0.000 (p < 0.05) and contributed the largest effective percentage at 78.32%. Collectively, talent management, the principal’s leadership, and student interest had a significant effect on student participation in extracurricular activities, with an F-calculated value of 488.440 and a coefficient of determination (R²) of 0.791. These findings indicate that student interest is a key factor in increasing student participation; therefore, it should be a primary focus in the development of extracurricular programs at schools.